A súmula vinculante no ordenamento jurídico brasileiro - Carvalho, Rony Cachola de (2008)
The present paper has as objective the study of instituting of the binding decision in the brazilian right. For that, was verified the existence or lack of harmony of the decision in face of the legal native system, as well as if such decision enunciateds could be inserted in basies theories of the right, such as: sources of the right, juridical hermeneutics, concretion of juridical norm. Other subjects strictly linked to the mechanism of the binding decision were also approached being analyzed together with the contrary and favorable positionings to the binding decision. It is verified that the bindign decision enunciated provides larger cohesion to the juridical system, in view of exert an orientation paper for elaboration of new laws and alteration of the existing, as well to signal for valid interpretations of the constitutional norms in certain period of time, promoting, like this, equality of judgements and larger previsibility of the right